Prevailing Trends of Violence against ‘Women Health Workers’ and their Psycho-Social Effects: Mapping Causes and Proposing Violence Mitigation Framework - Zulqarnain, Muhammad; Khan, Asim Muneeb; Aziz, Latafat; Abbas, Zaheer; Ali, Waris (International Journal of Psychosocial Rehabilitation, 2020)
The violence against health-care workers has become one of the serious global issues as between 8% and 38% of health workers faced physical violence during their service careers. The purpose of this research work was to look into the issue of violence against women health workers in Pakistan. The authors intended to address four associated questions in this research paper: a) What were the contemporary forms of violence faced by women health workers? b) What were major motives and causes which triggered the attitude of violence and extremism against women? c) How various forms of violence produced adverse effects on Psycho-social and economic aspects of society? d) What could be an appropriate framework to reduce and mitigate the frequency of violence? Qualitative research approach was employed for the collection, analysis and dedmonstration of data. The systematic review of literature revealed that there had been observed a remarkable increase in the ratio of violence which put the health profession at risk as well as threatened the lives of women workers. The most common forms of violence were physical and verbal and the main motives were psychological and social. The research also concluded that international organizations including WHO, ILO, ICN and PSI conducted research to diagnose reasons, develop framework, and suggest strategies but remained failed to handle the issue. It was therefore recommended to revise SOPs and make comprehensive theoretical and practical framework in context of geographical, social, political, economic, religious and cultural condition of Pakistan. It would also be beneficial if government would chalk out a separate plan to deal both: emergency and non-emergency situations. By keeping in view all dimensions of issue.